Professional artefacts: evaluating creative outcomes for work-based inquiry - Paula McIver Nottingham (Journal of Work-Applied Management, 2020)
Purpose – This paper aims to explore graduate perspectives about the creation and use of professional artefacts to communicate work-based inquiry projects to professional audiences. Design/methodology/approach – The study was based on constructivist qualitative interviews with 14 graduates from a part-time professional practice in arts programme and used thematic analysis to interpret and discuss the findings. Findings – Participants indicated a perceived value in the use of the professional artefact as a way of articulating their professional inquiry. Professional artefacts enable essential communication skills for professional contexts, have the capacity for engaging with professional audiences that are external to the university, have the potential for enabling further study and workplace employability, show awareness of project management and leadership capabilities and helped some individuals build on and share their own personal philosophy of practice with peer professionals. Research limitations/implications – As a small-scale research project that used purposive sampling, the findings are not representative, but could provide the creative means to develop professional artefacts within work-related educational programmes and workplace learning programmes. Practical implications – It is argued that the process and production of professional artefacts can provide the means for communicating work-based projects to professional audiences within workplace settings. Originality/value – Professional artefacts explore and present developmental aspects of work-based inquiries with distinctive creative approaches to favour practice knowledge and innovation that can be expressively shared with peer professionals.